Memahami Dan Mengatasi Pengabaian Emosional Dalam Pola Asuh Anak Usia Dini - Amelia Okta Fiana; Ismaniar Ismaniar; Lili Dasa Putri (CV. ITTC INDONESIA, 2025)
Emotional neglect is a form of parenting that is often unnoticed but has a significant impact on the development of young children. Although physical needs are met, children who do not receive emotional support such as affection, validation, attention, and responsiveness from their parents are at risk of experiencing psychological, social, and neurological developmental delays. This article aims to elaborate on the concept of emotional neglect in parenting, identify its characteristics, analyze causal factors, and explain its impact on child development. The research was conducted using the literature study method, examining books, scientific journals, and other relevant sources. The study results indicate that emotional neglect is closely linked to a permissive-negligent parenting style characterized by low parental warmth and involvement. The impact includes difficulties with emotional regulation, low self-esteem, behavioral problems, and even toxic stress that can affect a child's brain architecture. To address this issue, parents need to practice mindful parenting thru full emotional presence, warm communication, and consistent bonding activities. Thus, the effort to create a safe emotional environment becomes an important foundation for optimal child development.